2020
DOI: 10.3390/medicina56020070
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/Antioxidant Status of Breast Cancer Patients in Pre- and Post-Operative Periods

Abstract: Background and Objectives: The purpose of this study is to evaluate the level of oxidative stress before and after breast cancer surgery. Materials and Methods: Malondialdehyde (MDA) level was tested using a thiobarbituric acid (TBA) assay based on the release of a color complex due to TBA reaction with MDA. The glutathione S-transferase (GST) activity was evaluated by enzymatic conjugation of reduced glutathione (GSH) with 1-chloro-2,4-dinitrobenzene. The level of total glutathione (reduced GSH and oxidized G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…In addition, a lower ratio of GSH to GSSG in patients with Ewing’s sarcoma compared with OS patients was found. Lower levels of GSH + GSSG were observed before and after surgery in breast cancer patients by other authors [ 38 ]. Grunwell et al [ 39 ] found an increase in GSSG and a more oxidized redox state of GSH/GSSG in the serum of critically ill children aged 0–18 years (sepsis, asthma, solid tumors) compared with that of healthy children.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, a lower ratio of GSH to GSSG in patients with Ewing’s sarcoma compared with OS patients was found. Lower levels of GSH + GSSG were observed before and after surgery in breast cancer patients by other authors [ 38 ]. Grunwell et al [ 39 ] found an increase in GSSG and a more oxidized redox state of GSH/GSSG in the serum of critically ill children aged 0–18 years (sepsis, asthma, solid tumors) compared with that of healthy children.…”
Section: Discussionmentioning
confidence: 73%
“…On the contrary, a high concentration of reactive oxygen species (ROS) has been found in almost all cancers, due to increased metabolic activity, mitochondrial dysfunction, peroxisome activity, oncogenic activity, increased activity of oxidases, cyclooxygenases, lipoxygenases and thymidine phosphorylase [ 23 ]. Alterations in lipid peroxidation have been confirmed in breast cancer, and the main marker of oxidative stress is the level of malondialdehyde (MDA); likewise, a high level of serum MDA was found in the advanced cancer stage [ 24 ]. Reduced glutathione (GSH) is the most abundant thiol in cells, which plays an important role in antioxidant defense, acts as a free radical scavenger and detoxifying agent in cells, and is useful in a multitude of biochemical processes, such as cell proliferation, cell division and differentiation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in the redox level would cross this balance and occupied the potential to promote the oxidation level [22]. Didziapetriene J, et al [23] investigated that the antioxidant pathways and especially GSH levels are downregulated in breast cancer tissues Reduction in the ratios of GSH to GSSG were investigated in both serum and tissue samples of breast cancer patients as compared to serum and ANCT samples of the same patients. Our results are in agreement with already reported studies that the GSH and GSSG levels were decreased in breast cancer patients [23].…”
Section: Discussionmentioning
confidence: 99%